Religious Diversity and Philanthropy in Social Work Practices: Intervention Capital in Empowerment - Imam Alfi; Umi Halwati (UIN Sunan Kalijaga Yogyakarta, 2021)
This article focuses on how philanthropy and religious diversity become capital in the practice of social work. Qualitative research with a library research approach was used in this study. Data and information were carried out by searching libraries, books, documentation, journals or research results related to the object of research. Data analysis uses content analysis. This study found that religion is not only seen as an-sich doctrine, but as a social process so that it can reduce ideological clashes so as to create a harmonious life. Result also found that religious diversity as a national asset must be treated and preserved in humanitarian work. Religious diversity can be found through the social philanthropy movement for humanitarian programs. Through the philanthropic movement part of the capital in the intervention process. Community participation in a sustainable, targeted and organized manner is a meeting point. Thus, empowerment through the capital of religious pluralism and philanthropy can encourage a more just society's welfare. Keywords: Philanthropy, religious diversity, empowerment, social work intervention